Online attention of Covid-19 pre-prints on Twitter: Dissemination and thematic orientation analysis - Rocha, Eduardo Santos; Araújo, Ronaldo Ferreira de (Iberoamerican Journal of Science Measurement and Communication, 2021)
Objective. The online attention received by the pre-prints on covid-19 across Twitter was analyzed during the period January 2020-September 2021. Design/Methodology/Approach. The Covid-19 research in pre-print format was mapped using Dimensions as the data source. There were considered those articles with the highest circulation on Twitter. It was generated a classification of articles by thematic category and the tweets per category were counted. Besides, literature review, documentary research, content analysis, and altmetric analysis procedures were used. Results/Discussion. The 40 most disseminated pre-prints on the microblog were analyzed. They were framed into six categories, being 'Prevention' the most shared category with 245,367 tweets, followed by the 'Other' category with 84,281, 'Variants' with 81,391, and 'Transmission' with 81,135. The less shared categories were 'Clinical Studies' with 74,302 tweets and 'Treatment-Drugs' with 61,720. The majority of pre-prints dealt with topics related to covid-19 prevention, addressing topics like social distancing, use of masks, and vaccination. The most investigated categories were the ones with more online attention received, thus reflecting Twitter users’ interest in turning to research in the format of pre-prints with information sources about the covid-19 pandemic. Conclusions. Altmetrics technique has been useful to provide a greater understanding of the impact of covid-19 studies and its thematic orientation via the online attention received on Twitter.